Implementation of Mortgage Financing Through the Murabahah Bil Wakalah Contract at BTN Syariah Bank, Indramayu Branch Office - Fatkhudin; Didik Himmawan (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
Mortgage is a financing that makes it easier for people to meet their housing needs. Subsidized KPR BTN iB Syariah State Savings Bank (BTN) indramayu Branch Office itself is a home ownership financing product with subsidies from the government which is intended for low-income people (MBR). The background of this research is the use of the multi-contract murabahah bil wakalah Subsidized BTN KPR financing product at PT. State Savings Bank (BTN) Syariah indramayu Branch Office whose implementation is not yet certain whether it is in accordance with Bank Indonesia Regulation Number: 7/46/PBI/2005 Article 9 Paragraph 1 letter In this study, the author uses a type of field research conducted at the Sharia State Savings Bank (BTN) KCP Indramayu. While the research method used is a qualitative method and data collected through the method of observation, interview method, and method of documentation. The results of this study indicate that to determine the implementation of the murabahah bil wakalah contract in the iB Subsidized BTN KPR financing product at the Syariah State Savings Bank (BTN) Medan Branch Office. State Savings Bank (BTN) Syariah Indarmayu Branch Office according to or not in accordance with.